The Effects of Repeated Morphine Treatment on the Endogenous Cannabinoid System in the Ventral Tegmental Area - Zhang, Hong; Lipinski, Austin A.; Liktor-Busa, Erika; Smith, Angela F.; Moutal, Aubin; Khanna, Rajesh; Langlais, Paul R.; Largent-Milnes, Tally M.; Vanderah, Todd W. (Frontiers in Pharmacology, 2021)
The therapeutic utility of opioids is diminished by their ability to induce rewarding behaviors that may lead to opioid use disorder. Recently, the endogenous cannabinoid system has emerged as a hot topic in the study of opioid reward but relatively little is known about how repeated opioid exposure may affect the endogenous cannabinoid system in the mesolimbic reward circuitry. In the present study, we investigated how sustained morphine may modulate the endogenous cannabinoid system in the ventral tegmental area (VTA) of Sprague Dawley rats, a critical region in the mesolimbic reward circuitry. Studies here using proteomic analysis and quantitative real-time PCR (qRT-PCR) found that the VTA expresses 32 different proteins or genes related to the endogenous cannabinoid system; 3 of these proteins or genes (PLC2, ABHD6 and CB2R) were significantly affected after repeated morphine exposure (CB2R was only detected by qRT-PCR but not proteomics). We also identified that repeated morphine treatment does not alter either anandamide (AEA) or 2-arachidonoylglycerol (2-AG) levels in the VTA compared to saline treatment; however, there may be diminished levels of anandamide (AEA) production in the VTA 4 hours after a single morphine injection in both chronic saline and morphine pretreated cohorts. Treating the animals with an inhibitor of 2-AG degradation significantly decreased repeated opioid rewarding behavior. Taken together, our studies reveal a potential influence of sustained opioids on the endocannabinoid system in the VTA, suggesting that the endogenous cannabinoid system may participate in the opioid-induced reward.